2021
DOI: 10.1111/jce.15234
|View full text |Cite
|
Sign up to set email alerts
|

Distance between the descending aorta and the left inferior pulmonary vein as a determinant of biophysical parameters during paroxysmal atrial fibrillation cryoablation

Abstract: Introduction:The distance from the descending aorta (DA) to the posterior wall of the left atrium (LA) is variable. We aimed to determine whether the proximity between the DA and the left inferior pulmonary vein (LIPV) ostium has an impact on biophysical parameters and cryoballoon (CB) ablation efficacy during LIPV freezing.Methods: Patients referred for CB-ablation of atrial fibrillation (AF) in two highvolume centers were included. Cryoablation data were collected prospectively for each patient. The anatomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…The documented occurrence of pericardial effusion during catheterbased AF ablation varies between 0.5% and 4%, with cardiac tamponade observed in approximately 1% of cases (27,28). A recently published meta-analysis of randomized clinical trials (29), which included patients undergoing their initial atrial fibrillation ablation procedure, revealed an overall complication rate of 4.5%. In this analysis, the incidence of severe procedurerelated complications was 2.4%, which aligns with our findings.…”
Section: Safety and Feasibility Of The Single Transeptal Puncture App...mentioning
confidence: 99%
“…The documented occurrence of pericardial effusion during catheterbased AF ablation varies between 0.5% and 4%, with cardiac tamponade observed in approximately 1% of cases (27,28). A recently published meta-analysis of randomized clinical trials (29), which included patients undergoing their initial atrial fibrillation ablation procedure, revealed an overall complication rate of 4.5%. In this analysis, the incidence of severe procedurerelated complications was 2.4%, which aligns with our findings.…”
Section: Safety and Feasibility Of The Single Transeptal Puncture App...mentioning
confidence: 99%